The influence of accepting change, spirituality, and tenacity and competence on authentic leadership among novice teachers in Malaysia - Zolkipli, Noor Haifa; Mohamad, Mua’azam (Nurture, 2023)
Purpose: In schools, principals are leaders of teachers while teachers, are leaders of students and colleagues. The current development of the ever-changing education system makes the roles and responsibilities of teachers increasingly challenging. This requires a person to have an element of resilience to become a teacher who is responsible for guiding students and colleagues to achieve school goals. The aim of this study was to examine the influence of resilience (tenacity and competence, trusting in one’s instinct and tolerance of negative affect, acceptance of change and secure relationships, control, and spirituality) on authentic leadership among novice teachers, particularly in North Malaysia. Design/Methodology/Approach: This study used a quantitative approach through questionnaires such as The Connor-Davidson Resilience Scale and the Authentic Leadership Questionnaire (ALQ), involving a total of 229 novice teachers in the northern zone of Peninsular Malaysia as respondents. The data was analyzed using Statistical Package for the Social Sciences (SPSS) version 28 and Structural Equation Model-Part Least Square, SmartPLS 4 software. Findings: The findings showed that accepting change, spirituality, tenacity, and competence constructs have a significant and positive impact on authentic leadership. Conclusion: Resilience is a skill that teachers should have when influencing students and colleagues. Research Limitation: The data found in this study were based on questionnaires. The results of the information and findings of the study were limited as they depended on the honesty and willingness of the respondents to answer the questionnaire. Practical Implication: Spirituality in the workplace is among the key elements in achieving the organization's goals. Spirituality can help teachers have peace of mind when handling conflict. Teachers have to prepare physically and mentally to cope with the changes in organization because they are role models for colleagues and students. Contribution to Literature: This study contributes to the existing literature by demonstrating that resilience constructs have an influence on authentic leadership among novice teachers.